An agency perspective on firm diversification, efficiency and performance: evidence from Malaysia - Ng, Sin Huei; Boon, Heng Teh; Tze, San Ong (John Wiley and Sons, 2019)
We examine, from the agency perspective, the relationship between three important corporate measures among the Malaysian publicly-listed family-controlled firms: firm diversification, asset utilization efficiency and firm performance. We also explore the role of board independence in moderating the firm diversification-performance relationship. Our findings suggest that the greater the extent of firm diversification, the poorer will the asset utilization efficiency be. The poorer efficiency is likely to have caused the equally poorer performance for the firms in our findings. Notably, firm diversification is found to be more detrimental to performance for those firms affiliated to business group compared to firms without group affiliation. The group-affiliated firms which are found to be more diversified than the non-group firms, could have engaged in greater diversification for the self-interest of the controlling family. Specifically, we find that the agency-driven diversification causes the ROA (Tobin’s Q) of the firms to be lowered by 0.354% (0.026) for every additional increase in the number of business segments as the measure of firm diversification. In terms of the moderating effect of board independence, our finding shows that audit committee of board comprises entirely of independent outside directors positively moderate the firm diversification-performance linkage and is capable of reversing the apparently negative linkage between the two.